Metallization system as a part of thermal memory - Skvortsov, Arkadiy A.; Pshonkin, Danila E.; Volodina, Olga V.; Nikolaev, Vladimir K. (Heliyon, 2023)
This study aims to substantiate the potential of using “classical” metallization systems as microelectronic thermal memory cells. An experimental simulation is used to demonstrate that thermal information can be stored in memory for a certain time and then read without distortion. The possibility of using thin metal films on single-crystal silicon wafers as thermal memory cells is discussed. An experimental parametric study of “recording” thermal pulses and the temperature dynamics after their interruption is performed. This study uses rectangular current pulses with an amplitude of (1 … 6) × 1010 A/m2 and a duration of up to 1 ms. The temperature dynamics of a “thermal cell” are oscillographically studied up to the critical conditions when the contact area and metal film start degrading. The conditions of interconnections overheating up to the circuit break are considered. •The study shows the possibility of creating a thermal (phonon) memory cell based on a local surface heat source.•For the thermal cell the characteristic lifetimes of data in memory in described conditions were ∼300–500 μs.•The “critical” modes in which the structure was destroyed were j < 8 × 1010 A/m2, τ < 500 μs.